APPLYING PROJECT-BASED LEARNING TO REINFORCE THE STUDENTS’ CHARACTER - Astri Komara Putri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
21st -century skills become a concerning matter for all educators due to the challenges that the young generation will face in the future. And educators are on the essential duty to implement the proper teaching methods to support the students in achieving the competencies as well. The presence of "The 4Cs" (Communication, Collaboration, Critical Thinking, ProblemSolving, Creativity, and Innovation) as an indicator for learning outcomes are important components that cannot be separated in areas of life. These four skills are also included in the teaching and learning models named project-based learning. It is a teaching model that can lead students to experience an inquiry process. Students are expected to be able to develop knowledge, skills, and attitudes as the basic assessment for teachers in the context of character education The outline of this paper is that first the concept of Project-Based Learning, the overview of character education, and lastly reviewing a number of theories of 4Cs skills to strengthen character building for students